2022
DOI: 10.1021/jacs.1c09220
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Anthracene Clusters at Ice Surfaces

Abstract: Heterogeneous processes can control atmospheric composition. Snow and ice present important, but poorly understood, reaction media that can greatly alter the composition of air in the cryosphere in polar and temperate regions. Atmospheric scientists struggle to reconcile model predictions with field observations in snow-covered regions due to experimental challenges associated with monitoring reactions at air-ice interfaces, and debate regarding reaction kinetics and mechanisms has persisted for over a decade.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Because the FCS has a considerable volume and thickness compared to the QLL, the effect from the ice surface is considered negligible. However, in the FCS, a variety of interesting phenomena occur that are not predictable from bulk solutions of the same composition and temperature. In addition, freezing causes a significant change in the pH compared to its original value. It is known that salt depositions and the incorporation of ions into the ice crystal lattice are responsible for the pH shifts in frozen salt solutions. , We here report different intriguing pH behavior found in frozen salt solutions. The measured pH is significantly different from that predicted from the freeze concentration effect alone, and, in many cases, the pH appears to approach ∼7 by freezing.…”
Section: Introductionmentioning
confidence: 74%
“…Because the FCS has a considerable volume and thickness compared to the QLL, the effect from the ice surface is considered negligible. However, in the FCS, a variety of interesting phenomena occur that are not predictable from bulk solutions of the same composition and temperature. In addition, freezing causes a significant change in the pH compared to its original value. It is known that salt depositions and the incorporation of ions into the ice crystal lattice are responsible for the pH shifts in frozen salt solutions. , We here report different intriguing pH behavior found in frozen salt solutions. The measured pH is significantly different from that predicted from the freeze concentration effect alone, and, in many cases, the pH appears to approach ∼7 by freezing.…”
Section: Introductionmentioning
confidence: 74%
“…Ice provides water/ice interfaces and chemical environments and can greatly accelerate the reaction rate . For example, some recent studies have shown that the oxidation rate of nitrite and the reduction rate of halate can be accelerated by ice due to the freeze concentration effect. Ice can also increase the photodegradation rate of halobenzenes and the photodecarbonylation rate of dibenzyl ketones owing to the cage effect in ice. , Although it has been recognized that ice can improve the reactivity of chemicals, a clear picture of how ice surfaces relate to chemical transformations has remained elusive. , The chemical reactivity at ice surfaces differs greatly from that within complex ice matrixes. The reaction activity and selectivity are strongly determined by various physical and chemical properties of the ice surface, including the interfacial water-layering structure, two-dimensional confinement, and ice crystalline structure.…”
Section: Introductionmentioning
confidence: 99%
“…These results will provide insight into the confinement of water. The ideas of confinement we have developed in this work could enhance our understanding of anthracene cluster interactions with water ice 38 and in anthracene dimer exciplex formation in solution, 39 both of which have relevance in a wide variety of sub-disciplines.…”
mentioning
confidence: 99%